2007
DOI: 10.1073/pnas.0609642104
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the connection domain of HIV-1 reverse transcriptase increase 3′-azido-3′-deoxythymidine resistance

Abstract: We previously proposed that a balance between nucleotide excision and template RNA degradation plays an important role in nucleoside reverse transcriptase inhibitor (NRTI) resistance. To explore the predictions of this concept, we analyzed the role of patient-derived C-terminal domains of HIV-1 reverse transcriptase (RT) in NRTI resistance. We found that when the polymerase domain contained previously described thymidine analog resistance mutations, mutations in the connection domain increased resistance to 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
162
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(179 citation statements)
references
References 24 publications
16
162
0
Order By: Relevance
“…In this case, RNase H cleavage appears to force the release of the primer at early time points, and the primer does not rebind to the enzyme under these conditions. The release of the primer is less efficient with the mutant enzyme, which provides experimental evidence for the hypothesis that connection domain mutations can delay the irreversible degradation of the DNA⅐RNA substrate (33).…”
Section: Connection Domain Mutations A360v and N348i Increase Atpmedimentioning
confidence: 85%
See 3 more Smart Citations
“…In this case, RNase H cleavage appears to force the release of the primer at early time points, and the primer does not rebind to the enzyme under these conditions. The release of the primer is less efficient with the mutant enzyme, which provides experimental evidence for the hypothesis that connection domain mutations can delay the irreversible degradation of the DNA⅐RNA substrate (33).…”
Section: Connection Domain Mutations A360v and N348i Increase Atpmedimentioning
confidence: 85%
“…Substrates-The combination of A360V and N348I, when present against a background of TAMs was shown to amplify resistance to AZT but not to d4T (33). The crucial role played by TAMs suggests that the combination of TAMs and connection domain mutations further increase efficiency of ATP-mediated AZT-MP excision.…”
Section: Connection Domain Mutations A360v and N348i Increase Atpmedimentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in HIV-1 RT that confer resistance to the NRTI, 3Ј-azidothymidine, increase rates of excision (15)(16)(17)(18)(19)(20)(21). More recently, it has been shown that mutations in the connection and RNase H domains of HIV-1 RT confer resistance to NRTIs and NNRTIs (9,10,(22)(23)(24)(25)(26). These mutations appear to exert their effects on susceptibility to 3Ј-azidothymidine more indirectly.…”
Section: Hiv-1mentioning
confidence: 99%